P-30 Changing attitudes and behaviours towards digital legacy and digital assets. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Norris, James; Taubert, Mark
Abstract : Background: The Internet is the biggest and most 'disruptive' force since the industrial revolution. As a result, society is spending an ever increasing amount of time online. This has led to a range of benefits whilst changing the way in which society prepares for death, mourns and remembers the deceased into posterity. Each year the Digital Legacy Association carry out the Digital Death Survey. Aims: The aim of the Digital Death Survey is to explore society's attitudes towards death and dying in today's digital world. Asking questions through such a survey and openly publishing the results helps evoke discussions around 'digital death' and the implications not planning for death digitally can have. The aim of the 'Changing attitudes and behaviours towards digital legacy and digital assets planning' poster will be to display this year's data. We will do so by cross-referencing this year's data with data from the previous two years. Methods: Cross reference data, explore year on year changes, draw conclusions and predict trends. We launched the Digital Death Survey at EAPC 2016. The survey coincided with the first interactive poster that displays real time data on it. Results: 300 people have completed the survey thus far. We expect 500 people to have completed it by the end of July when the survey ends. We plan to display the data digitally (via an iPad) on the poster and through images on the poster.